Industrial supplier-manufacturer relationship and environmental dynamism on strategic outsourcing success: A conceptual study - Hassan, Mohamad Ghozali; Razalli, Mohd Rizal; Abdul Talib, Asmat Nizam (Penerbit UTM Press, 2015)
Poor outsourcing performance of a manufacturing industry could be improved through relational-oriented exchanges and its antecedents.Researches that examine the link among relational-oriented exchanges and their antecedents, environmental dynamism, and outsourcing performances in the manufacturing industry are still in its early development stage.Owing to high competition and risks in a manufacturing environment, the present study aims at conceptualizing a framework that examines the link between relational-oriented exchanges, the antecedents of relational-oriented exchanges, environmental dynamism, and outsourcing performances by recommending environmental dynamism as a moderator on the link between relational oriented exchanges and outsourcing performances.The research will be beneficial to the practitioners, as it will identify the utilization of environmental dynamism as the supplier’s ability of adapting to novel conditions and to maximize confidence in their partners’ future activities.